Policy Analysis of Free Public WiFi Facilities as an Effort to Advance Banda Aceh’s Development into a Smart City - Hanunawati Hanunawati; Siti Nur Zalikha; Taufik Taufik (Journal of Aceh Studies, 2027)
Advancements in information technology have prompted local governments to enhance digital-based public services through the implementation of the Smart Cityconcept. One initiative undertaken by the Banda Aceh City Government is the provision of free WiFi facilities in several public parks to ensure equitable internet access and improve public digital literacy. However, implementation faces various challenges, such as limited free WiFi network capacity, equipment malfunctions, low public digital literacy, and a lack of public concern regarding the preservation of public facilities. This study aims to analyze the implementation of the free WiFi provision policy in Banda Aceh’s public parks in support of Smart City development. A qualitative research method with a descriptive approach was employed. Data were gathered through interviews, observation, and documentation involving informants from the Banda Aceh City Communication, Informatics, and Statistics Agency (Diskominfotik), technical staff, park security personnel, and members of the public including students who use the free WiFi. Data analysis was conducted using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The results indicate that the policy implementation has proceeded reasonably well based on the dimensions of "Content of Policy" and "Context of Implementation" as defined by Merilee S. Grindle. The program has yielded benefits by increasing internet access and supporting educational activities, public services, and the community's digital economic activities. Nevertheless, implementation still faces obstacles such as limited network infrastructure, technical disruptions, and suboptimal digital literacy and public participation in maintaining the free WiFi facilities. Therefore, improvements in network capacity, infrastructure maintenance, service coverage expansion, and strengthened digital literacy education are required to ensure the success of Smart Citydevelopment in Banda Aceh.